Child Passenger Safety Technician Consultation in the Pediatric Primary Care Setting. (September 2017) - Burstein, Dina; Zonfrillo, Mark R.; Baird, Janette; Mello, Michael J.
Correct use of a child safety seat (CSS) can reduce the risk of fatal motor vehicle crash–related injury by up to 71%; however, misuse rates for CSS are as high as 70%. We recruited 189 caregivers at 2 large suburban pediatric office practices; 94 in the intervention group and 95 in the control group. All participants completed a baseline survey and received a CSS safety brochure. Intervention participants had their CSS installation checked at enrollment by a certified child passenger safety (CPS) technician. Follow-up was conducted 4 months post enrollment. Intervention group participants had a 21.3% reduction in critical misuse at follow-up, whereas control participants critical misuse rate at follow-up was identical to the intervention group at baseline. A consult with a certified CPS technician, at the time of a routine visit to the pediatrician, resulted in a reduction in CSS misuse rates.